Artificial marble and preparation method thereof

By using materials such as aliphatic polyisocyanate and cellulose ether modified magnesium silicate in artificial marble, the problems of oxidative discoloration and mechanical properties of artificial marble are solved, and higher weather resistance, mechanical strength and flame retardancy are achieved.

CN119638268AActive Publication Date: 2025-03-18WUHAN WOERPU TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411964476.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-18
Estimated Expiration
2044-12-30

Smart Images

  • Figure BDA0005218008800000091
    Figure BDA0005218008800000091
  • Figure BDA0005218008800000101
    Figure BDA0005218008800000101
  • Figure BDA0005218008800000131
    Figure BDA0005218008800000131
Patent Text Reader

Abstract

The invention relates to the technical field of artificial stone, in particular to artificial marble and a preparation method thereof. The artificial marble provided by the invention is prepared from the following components in parts by weight: 100 parts of marble powder, 8 to 12 parts of aliphatic polyisocyanate, 20 to 30 parts of polypropylene glycol, 0.2 to 0.3 part of dibutyltin dilaurate, 10 to 15 parts of cellulose ether modified magnesium lithium silicate, 5 to 7.5 parts of polyvinyl acetate and 2 to 3 parts of flame retardant. Aliphatic polyisocyanate is adopted to replace unsaturated polyester resin, unsaturated double bonds in a system are reduced, then cellulose ether modified magnesium lithium silicate and polyvinyl acetate are matched to improve the mechanical performance of the marble, and therefore the artificial marble with excellent weather resistance, stain resistance, mechanical strength and flame retardance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of artificial stone, and more specifically, to an artificial marble and a preparation method thereof. Background Art

[0002] Artificial marble is a synthetic decorative material with the advantages of good product gloss, bright and rich colors, strong processability, good decorative effect, etc. It is cheaper than natural marble, so it is widely used in the field of architectural decoration.

[0003] At present, organic artificial marble mainly uses natural marble as filler, uses unsaturated polyester resin and other curable materials as the matrix, and then adds flame retardants and other additives to cure and form. However, common unsaturated polyester resins often do not react completely during curing and leave unsaturated double bonds. When used for a long time, especially in outdoor conditions, they will be oxidized, causing the organic artificial marble to change color and turn yellow. At the same time, it will also affect its mechanical properties, resulting in problems such as cracking, warping and deformation. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the present application provides an artificial marble and a preparation method thereof. The present invention adopts aliphatic polyisocyanate to replace unsaturated polyester resin to reduce the unsaturated double bonds in the system, and then cooperates with cellulose ether to modify lithium magnesium silicate and polyvinyl acetate to improve the mechanical properties of marble, thereby obtaining artificial marble with excellent weather resistance, stain resistance, mechanical strength and flame retardancy.

[0005] In a first aspect, the present application provides an artificial marble comprising the following components in parts by weight: 100 parts of marble powder, 8-12 parts of aliphatic polyisocyanate, 20-30 parts of polypropylene glycol, 0.2-0.3 parts of dibutyltin dilaurate, 10-15 parts of cellulose ether modified lithium magnesium silicate, 5-7.5 parts of polyvinyl acetate, and 2-3 parts of flame retardant.

[0006] The present invention uses marble as a filler and utilizes aliphatic polyisocyanate to react with polypropylene glycol to produce polyurethane, which is not easy to yellow and has excellent weather resistance; dibutyltin dilaurate can significantly increase the reaction rate in the polyurethane synthesis process, specifically by interacting with isocyanate and hydroxyl reactants to reduce the activation energy of the reaction, thereby accelerating the reaction process;

[0007] However, dibutyltin dilaurate is easy to precipitate into solids at low temperatures, affecting the color and appearance of artificial marble. For this reason, cellulose ether-modified lithium magnesium silicate is used in combination in the present application. The lithium magnesium silicate is a trioctahedral layered silicate mineral. Since its thin sheet surface is negatively charged and its end face is positively charged, the end face of the separated thin sheet is attracted to the surface of another thin sheet, thereby quickly forming a three-dimensional colloidal structure, which can effectively adsorb dibutyltin dilaurate and reduce its precipitation; the cellulose ether can not only increase the compatibility of lithium magnesium silicate, polyurethane and marble powder, but also increase the hydroxyl content in the molecular structure; the aliphatic polyisocyanate in the system can also combine with the cellulose ether-modified lithium magnesium silicate under the action of dibutyltin dilaurate, thereby increasing the cross-linked network formed by polyurethane, so that the obtained artificial marble has excellent mechanical strength;

[0008] On this basis, the present application also adds an appropriate amount of polyvinyl acetate. Polyvinyl acetate has good compatibility with marble powder and cellulose ether-modified lithium magnesium silicate. In the present application, polyvinyl acetate can, on the one hand, promote uniform dispersion among marble powder, polyurethane and cellulose ether-modified lithium magnesium silicate, thereby improving the film-forming property of the system. On the other hand, the hydroxyl groups in polyvinyl acetate can also react with isocyanate groups to form cross-links, thereby further improving the weather resistance, stain resistance and mechanical strength of the artificial marble.

[0009] Preferably, the weight ratio of the aliphatic polyisocyanate to the polypropylene glycol is 2:5.

[0010] By adopting the above technical solution, a portion of aliphatic polyisocyanate remains after the reaction with polypropylene glycol, and the excess aliphatic polyisocyanate can better combine with cellulose ether-modified lithium magnesium silicate, thereby facilitating the effective formation of a cross-linked network in the system.

[0011] Preferably, the weight ratio of the cellulose ether modified lithium magnesium silicate to the aliphatic polyisocyanate is 6:5.

[0012] By adopting the above technical solution, if the amount of cellulose ether-modified lithium magnesium silicate is too much, the viscosity of the system will increase, and then the dispersion difficulty of marble powder and polyurethane will increase; if the amount of cellulose ether-modified lithium magnesium silicate is too little, it is difficult to effectively lock dibutyltin dilaurate and marble powder; therefore, the amount of cellulose ether-modified lithium magnesium silicate in this application needs to be strictly controlled, preferably with the above weight ratio.

[0013] Preferably, the weight ratio of the cellulose ether modified lithium magnesium silicate to the polyvinyl acetate is 2:1.

[0014] When using the above technical solution, if the amount of polyvinyl acetate used is too much, it will affect the brittleness of the artificial marble to a certain extent. If the amount of polyvinyl acetate used is too little, it is difficult to effectively play a dispersing role. In this application, the above weight ratio is appropriate.

[0015] Preferably, the preparation method of the cellulose ether modified lithium magnesium silicate comprises the following steps: taking an appropriate amount of water, first adding cellulose ether to disperse evenly, then adding lithium magnesium silicate to continue to disperse evenly, and then drying to remove water to obtain the cellulose ether modified lithium magnesium silicate.

[0016] Preferably, the weight ratio of the lithium magnesium silicate to the cellulose ether is 1:0.2-0.5.

[0017] The present application utilizes water to evenly disperse cellulose ether and lithium magnesium silicate, which has simple operation, good dispersion effect, and convenient subsequent water removal; in the preparation method, cellulose ether is first dispersed, which is conducive to better coating of cellulose ether on the surface of lithium magnesium silicate molecules and improving the modification effect of cellulose ether, wherein the amount of cellulose ether needs to be strictly controlled. If the content of cellulose ether is too much, it will affect the water resistance of artificial marble. If the content of cellulose ether is too little, the modification effect of cellulose ether on lithium magnesium silicate is poor, thereby affecting the dispersion effect of lithium magnesium silicate in the system.

[0018] Preferably, the cellulose ether is a mixture of hydroxyethyl cellulose 250HBR and hydroxyethyl cellulose 250HHBR.

[0019] Preferably, the weight ratio of the hydroxyethyl cellulose 250HBR to the hydroxyethyl cellulose 250HHBR is 1:1.

[0020] The cellulose ether in the cellulose ether-modified lithium magnesium silicate of the present application can also coat the color points in the marble powder, so as to ensure the bright color of the artificial marble. However, the molecular structures of different cellulose ethers are quite different, which has a great influence on the morphology and stability of the color points in the marble powder. For example, hydroxyethyl cellulose 250HBR, when the amount added is small, the color points are fragile, but after reaching a certain amount, the color points are not easy to break, but the artificial marble prepared by it is more brittle; while hydroxyethyl cellulose 250HHBR, at the same addition amount, the color points are not easy to break, and the artificial marble prepared by it is less brittle, but when it exceeds a certain amount, the brittleness of the artificial marble will also increase. This may be caused by the different relative molecular masses of the two. The average relative molecular weight of 250HBR is 30,000, and the molecular chain is relatively short. When the amount is small, the color points are fragile, but when the amount is large, due to the large number of cross-linking points with lithium magnesium silicate, the subsequent brittleness is large. The average relative molecular weight of 250HHBR is 100,000, and the molecular chain is relatively long. When used in an appropriate amount, it can achieve a balance between encapsulation and cross-linking with lithium magnesium silicate, and obtain artificial marble with less brittle color points. Therefore, by strictly controlling the type and amount of cellulose ether, the cellulose ether-modified lithium magnesium silicate obtained can not only effectively maintain the color stability of artificial marble, but also further improve the mechanical strength of artificial marble.

[0021] Preferably, the flame retardant is a silicon-based flame retardant.

[0022] Silicon-based flame retardants have the characteristics of high efficiency, low toxicity, anti-dripping, easy carbonization, and smoke suppression, including flame retardants such as siloxane, inorganic silicon-based, and organic-inorganic hybrid silicon-based. In the present application, the above-mentioned silicon-based flame retardants can be well dispersed in the system to effectively exert the flame retardant effect.

[0023] In a second aspect, the present application provides a method for preparing artificial marble, comprising the following steps:

[0024] Preliminarily mix a set amount of marble powder, polypropylene glycol, cellulose ether-modified lithium magnesium silicate and polyvinyl acetate to obtain a mixture;

[0025] Add a set amount of aliphatic polyisocyanate and flame retardant into the mixture and continue to mix well, then add dibutyltin dilaurate and stir well to obtain a pre-cured material;

[0026] The pre-cured material is put into a mold for compression molding, and then is heat-cured by heat preservation and then cooled and demoulded to obtain the artificial marble.

[0027] Both cellulose ether modified lithium magnesium silicate and polyvinyl acetate have certain hydrophilicity. In the present application, cellulose ether modified lithium magnesium silicate, polyvinyl acetate and marble powder are firstly dispersed evenly with polypropylene glycol, which can effectively reduce the agglomeration phenomenon compared with directly adding marble powder into aliphatic polyisocyanate; then aliphatic polyisocyanate is added and mixed evenly. At this time, the reaction in the system is slow due to the lack of catalyst, which helps to fully disperse the components first, and finally the catalyst is added to accelerate the generation of polyurethane, so that the artificial marble obtained has better anti-color bleeding, weather resistance and mechanical strength.

[0028] In summary, this application has the following beneficial effects:

[0029] 1. This application uses aliphatic polyisocyanate to replace unsaturated polyester resin, and uses cellulose ether-modified lithium magnesium silicate and polyvinyl acetate in combination, which can not only effectively slow down the oxidation and yellowing of artificial marble, but also has excellent weather resistance, stain resistance, mechanical strength and flame retardancy.

[0030] 2. The present application strictly controls the weight ratio of aliphatic polyisocyanate to polypropylene glycol, cellulose ether-modified lithium magnesium silicate and polyvinyl acetate, so that the reaction parameters of the system are maintained in a dynamic equilibrium state, thereby further improving the weather resistance, stain resistance and mechanical strength of artificial marble.

[0031] 3. This application further limits the cellulose ether-modified lithium magnesium silicate, thereby making the artificial marble have better weather resistance and mechanical strength.

[0032] 4. When preparing artificial marble, the present application strictly controls the order of adding components to ensure that the components are fully dispersed, so that the artificial marble obtained has better weather resistance and mechanical strength. DETAILED DESCRIPTION

[0033] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0034] The raw materials used in this application are all commercially available products, among which the marble powder has a specification of 400 mesh; the aliphatic polyisocyanate is Rhodia products XFD 90 B is used as an example to illustrate, its average relative molecular weight is 666, and its purity is 99%; the CAS number of polypropylene glycol is 25322-69-4, and its average molecular weight is 2025; the CAS number of dibutyltin dilaurate is 77-58-7, and its purity is 95%; polyvinyl acetate is used as an example to illustrate the product of Shanghai Aladdin product number P304876, CAS number is 9003-20-7, it is light yellow transparent glass-like particles, and the effective ingredient content is 99%; The flame retardant is illustrated by taking methylphenyl polysiloxane, diphenyl dimethyl polysiloxane and triisopropylphenyl phosphate (IPPP50) as examples; the cellulose ether is illustrated by taking hydroxyethyl cellulose 250HBR, hydroxyethyl cellulose 250HHBR and methyl cellulose (350-550 MPA·S, 2% aqueous solution at 20°C) as examples; the CAS number of lithium magnesium silicate is 37220-90-9, the purity is 99%, and the dispersion viscosity (5% solid content) is 3000 cps.

[0035] Preparation example of cellulose ether modified lithium magnesium silicate

[0036] Preparation Example 1

[0037] This preparation example provides a preparation method of cellulose ether modified lithium magnesium silicate, comprising the following steps: taking 200g of water, first adding 20g of hydroxyethyl cellulose 250HBR and 20g of hydroxyethyl cellulose 250HHBR and dispersing them evenly, then adding 100g of lithium magnesium silicate and continuing to disperse them evenly, and then drying to remove water to obtain cellulose ether modified lithium magnesium silicate a.

[0038] Preparation Example 2

[0039] This preparation example provides a preparation method of cellulose ether modified lithium magnesium silicate, comprising the following steps: taking 200g of water, first adding 5g of hydroxyethyl cellulose 250HBR and 5g of hydroxyethyl cellulose 250HHBR and dispersing them evenly, then adding 100g of lithium magnesium silicate and continuing to disperse them evenly, and then drying to remove moisture to obtain cellulose ether modified lithium magnesium silicate b.

[0040] Preparation Example 3

[0041] This preparation example provides a preparation method of cellulose ether modified lithium magnesium silicate, comprising the following steps: taking 200g of water, first adding 10g of hydroxyethyl cellulose 250HBR and 10g of hydroxyethyl cellulose 250HHBR and dispersing them evenly, then adding 100g of lithium magnesium silicate and continuing to disperse them evenly, and then drying to remove moisture to obtain cellulose ether modified lithium magnesium silicate c.

[0042] Preparation Example 4

[0043] This preparation example provides a preparation method of cellulose ether modified lithium magnesium silicate, comprising the following steps: taking 200g of water, first adding 25g of hydroxyethyl cellulose 250HBR and 25g of hydroxyethyl cellulose 250HHBR and dispersing them evenly, then adding 100g of lithium magnesium silicate and continuing to disperse them evenly, and then drying to remove moisture to obtain cellulose ether modified lithium magnesium silicate d.

[0044] Preparation Example 5

[0045] This preparation example provides a preparation method of cellulose ether modified lithium magnesium silicate, comprising the following steps: taking 200g of water, first adding 30g of hydroxyethyl cellulose 250HBR and 30g of hydroxyethyl cellulose 250HHBR and dispersing them evenly, then adding 100g of lithium magnesium silicate and continuing to disperse them evenly, and then drying to remove moisture to obtain cellulose ether modified lithium magnesium silicate e.

[0046] Preparation Example 6

[0047] This preparation example provides a preparation method of cellulose ether modified lithium magnesium silicate, comprising the following steps: taking 200g of water, first adding 10g of hydroxyethyl cellulose 250HBR and 30g of hydroxyethyl cellulose 250HHBR and dispersing them evenly, then adding 100g of lithium magnesium silicate and continuing to disperse them evenly, and then drying to remove moisture to obtain cellulose ether modified lithium magnesium silicate f.

[0048] Preparation Example 7

[0049] This preparation example provides a preparation method of cellulose ether modified lithium magnesium silicate, comprising the following steps: taking 200g of water, first adding 30g of hydroxyethyl cellulose 250HBR and 10g of hydroxyethyl cellulose 250HHBR and dispersing them evenly, then adding 100g of lithium magnesium silicate and continuing to disperse them evenly, and then drying to remove water to obtain cellulose ether modified lithium magnesium silicate g.

[0050] Preparation Example 8

[0051] This preparation example provides a preparation method of cellulose ether modified lithium magnesium silicate, comprising the following steps: taking 200g of water, first adding 20g of methyl cellulose and 20g of hydroxyethyl cellulose 250HHBR and dispersing them evenly, then adding 100g of lithium magnesium silicate and continuing to disperse them evenly, and then drying to remove moisture to obtain cellulose ether modified lithium magnesium silicate h.

[0052] Preparation Example 9

[0053] This preparation example provides a preparation method of cellulose ether modified lithium magnesium silicate, comprising the following steps: taking 200g of water, first adding 40g of hydroxyethyl cellulose 250HHBR and dispersing it evenly, then adding 100g of lithium magnesium silicate and continuing to disperse it evenly, and then drying to remove water to obtain cellulose ether modified lithium magnesium silicate i.

[0054] Preparation Example 10

[0055] This preparation example provides a preparation method of cellulose ether modified lithium magnesium silicate, comprising the following steps: taking 200g of water, first adding 40g of hydroxyethyl cellulose 250HBR and dispersing it evenly, then adding 100g of lithium magnesium silicate and continuing to disperse it evenly, and then drying to remove water to obtain cellulose ether modified lithium magnesium silicate i.

[0056] The present application is further described in detail below in conjunction with embodiments and comparative examples.

[0057] Example

[0058] Example 1

[0059] This embodiment provides a method for preparing artificial marble, comprising the following steps:

[0060] ① Preliminarily mix 1000g of marble powder, 250g of polypropylene glycol, 120g of cellulose ether-modified lithium magnesium silicate a and 60g of polyvinyl acetate to obtain a mixture;

[0061] ②, add 100g of aliphatic polyisocyanate and 25g of methylphenyl polysiloxane into the mixture and continue to mix, then add 2.5g of dibutyltin dilaurate and stir well to obtain a pre-cured material;

[0062] ③. Put the pre-cured material into the mold for pressing and curing at 90°C for 30 minutes. After curing, cool and demould to obtain artificial marble.

[0063] Embodiment 2-4

[0064] Examples 2-4 are based on the method of Example 1, with the amounts of components adjusted. For specific adjustments, see Table 1 below.

[0065] Table 1 Component dosage table of Examples 1-4 (unit: g)

[0066]

[0067]

[0068] Embodiment 5-6

[0069] In Examples 5-6, based on the method of Example 1, the weight ratio of aliphatic polyisocyanate and polypropylene glycol is adjusted. For specific adjustments, see Table 1 above.

[0070] Embodiment 7-8

[0071] In Examples 7-8, based on the method of Example 1, the weight ratio of cellulose ether-modified lithium magnesium silicate to aliphatic polyisocyanate is adjusted. For specific adjustment details, see Table 1 above.

[0072] Examples 9-10

[0073] In Examples 9-10, based on the method of Example 1, the weight ratio of cellulose ether-modified lithium magnesium silicate to polyvinyl acetate is adjusted. For specific adjustment details, see Table 1 above.

[0074] Examples 11-19

[0075] Examples 11-19 are based on the method of Example 1, and cellulose ether-modified lithium magnesium silicate a is replaced. Among them, Example 11 uses cellulose ether-modified lithium magnesium silicate b prepared in Preparation Example 2; Example 12 uses cellulose ether-modified lithium magnesium silicate c prepared in Preparation Example 3; Example 13 uses cellulose ether-modified lithium magnesium silicate d prepared in Preparation Example 4; Example 14 uses cellulose ether-modified lithium magnesium silicate e prepared in Preparation Example 5; Example 15 uses cellulose ether-modified lithium magnesium silicate f prepared in Preparation Example 6; Example 16 uses cellulose ether-modified lithium magnesium silicate g prepared in Preparation Example 7; Example 17 uses cellulose ether-modified lithium magnesium silicate h prepared in Preparation Example 8; Example 18 uses cellulose ether-modified lithium magnesium silicate i prepared in Preparation Example 9; Example 19 uses cellulose ether-modified lithium magnesium silicate j prepared in Preparation Example 10.

[0076] Examples 20-21

[0077] Examples 20-21 are based on the method of Example 1, but the flame retardant methylphenyl polysiloxane is replaced. The flame retardant used in Example 20 is diphenyl dimethyl polysiloxane; the flame retardant used in Example 21 is triisopropylphenyl phosphate.

[0078] Embodiment 22

[0079] Example 22 is based on the component formula of Example 1, and the preparation method is adjusted, and specifically includes the following steps:

[0080] ①, preliminarily mix 1000g of marble powder, 100g of aliphatic polyisocyanate, 350g of polypropylene glycol, 2.5g of dibutyltin dilaurate and 25g of methylphenylpolysiloxane to obtain a mixture;

[0081] ②, add 120g of cellulose ether modified lithium magnesium silicate a and 60g of polyvinyl acetate into the mixture and continue to mix to obtain a pre-cured material;

[0082] ③. Put the pre-cured material into the mold for pressing and curing at 90°C for 30 minutes. After curing, cool and demould to obtain artificial marble.

[0083] Comparative Example

[0084] Comparative Example 1

[0085] In this comparative example, based on the method of Example 1, an equal amount of lithium magnesium silicate was used to replace the cellulose ether-modified lithium magnesium silicate a.

[0086] Comparative Example 2

[0087] In this comparative example, based on the method of Example 1, a mixture of 20 g of hydroxyethyl cellulose 250HBR, 20 g of hydroxyethyl cellulose 250HHBR and 100 g of lithium magnesium silicate was used to replace the cellulose ether-modified lithium magnesium silicate a.

[0088] Comparative Example 3

[0089] In this comparative example, based on the method of Example 1, an equal amount of polyvinyl acetate was used to replace the cellulose ether-modified lithium magnesium silicate a.

[0090] Comparative Example 4

[0091] In this comparative example, based on the method of Example 1, an equal amount of cellulose ether-modified lithium magnesium silicate a was used to replace polyvinyl acetate.

[0092] Comparative Example 5

[0093] This comparative example provides a method for preparing artificial marble, comprising the following steps:

[0094] ① Preliminarily mix 1000g of marble powder, 120g of cellulose ether-modified lithium magnesium silicate a and 60g of polyvinyl acetate to obtain a mixture;

[0095] ②, add 452.5g of bisphenol A type unsaturated polyester resin (model 3301C) and 25g of methylphenyl polysiloxane into the mixture and continue to mix to obtain a pre-cured material;

[0096] ③. Put the pre-cured material into the mold for pressing and curing at 90°C for 30 minutes. After curing, cool and demould to obtain artificial marble.

[0097] Performance testing

[0098] The artificial marbles prepared in Examples 1-22 and Comparative Examples 1-5 of the present application were used as samples to perform the following performance tests. The test results are shown in Table 2 below.

[0099] 1. Weather resistance: The gloss retention rate of the sample before and after UV aging treatment is used to illustrate the glossiness. The glossiness is the mirror glossiness, and the incident angle is 60°. The UV aging treatment of the sample refers to the standard GB / T 16422.3-2014. The lamp type is 1A (UVA-340) fluorescent UV lamp, the exposure cycle is 8h drying + 4h condensation, and the irradiance is 0.76W / m at 340nm. 2 / nm, radiation temperature is 60±3℃;

[0100] 2. Stain resistance: Soak the sample in a mixture of water and edible oil in a ratio of 1:1 for 48 hours, then take it out and observe whether there is any stain on the surface of the sample;

[0101] 3. Mechanical strength: Use physical and mechanical properties to illustrate, refer to standard DB44 / T768-2010 "Resin-type artificial stone slabs" for details;

[0102] 4. Flame retardant performance: It is illustrated by the limiting oxygen index and the comparative combustion characteristics of solid plastics in a vertical position. The specific reference standards are ASTM D-2836 and ASTM D-3801.

[0103] Table 2 Performance test results of Examples 1-22 and Comparative Examples 1-5

[0104]

[0105]

[0106] Referring to Table 2, combined with the test results of Examples 1 to 4 and Comparative Examples 1 to 5, it can be obtained that the present application uses aliphatic polyisocyanate to replace the unsaturated polyester resin, and uses cellulose ether-modified lithium magnesium silicate and polyvinyl acetate in combination, and the cellulose ether-modified lithium magnesium silicate and polyvinyl acetate cannot be replaced at will, and the artificial marble prepared thereby has excellent weather resistance, stain resistance, mechanical strength and flame retardancy.

[0107] By comparing the test results of Example 1 with those of Examples 5 to 10, it can be found that the adjustment of the amounts of aliphatic polyisocyanate, polypropylene glycol, cellulose ether-modified lithium magnesium silicate and polyvinyl acetate in the present application uniformly affects the performance of the artificial marble. In the present application, when the weight ratio of aliphatic polyisocyanate to polypropylene glycol is strictly controlled to be 2:7, the weight ratio of cellulose ether-modified lithium magnesium silicate to aliphatic polyisocyanate is 6:5, and the weight ratio of cellulose ether-modified lithium magnesium silicate to polyvinyl acetate is 2:1, the obtained artificial marble has higher gloss retention, compression strength, bending strength and limiting oxygen index, and also has better stain resistance, so it is further preferred.

[0108] By comparing the test results of Example 1 with those of Examples 11 to 19, it can be found that in the cellulose ether-modified lithium magnesium silicate used in the present application, when the weight ratio of lithium magnesium silicate to cellulose ether is 1:0.2-0.5, and the cellulose ether is compounded by hydroxyethyl cellulose 250HBR and hydroxyethyl cellulose 250HHBR in a weight ratio of 1:1, the corresponding artificial marble has a higher gloss retention rate, better stain resistance and mechanical properties.

[0109] By comparing the test results of Example 1 with those of Examples 20 to 21, it can be concluded that the silicon-based flame retardant used in the present application has better flame retardant properties than other flame retardants, among which methylphenyl polysiloxane is further preferred. This may be because the molecular weight of methylphenyl polysiloxane is relatively small, and it can achieve uniform dispersion while quickly migrating to the surface of the artificial marble for flame retardancy when combustion occurs, so it is further preferred.

[0110] By comparing the test results of Example 1 with those of Example 22, it can be concluded that when preparing artificial marble in the present application, the different order of adding components will affect the performance of the artificial marble to a certain extent. For this reason, the present application strictly controls the order of adding components to ensure that the components are fully dispersed, so that the artificial marble obtained has better weather resistance and mechanical strength.

[0111] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An artificial marble, characterized in that: The invention comprises the following components in parts by weight: 100 parts of marble powder, 8-12 parts of aliphatic polyisocyanate, 20-30 parts of polypropylene glycol, 0.2-0.3 parts of dibutyltin dilaurate, 10-15 parts of cellulose ether modified lithium magnesium silicate, 5-7.5 parts of polyvinyl acetate and 2-3 parts of flame retardant.

2. The artificial marble according to claim 1, characterized in that: The weight ratio of the aliphatic polyisocyanate to the polypropylene glycol is 2:

5.

3. The artificial marble according to claim 1, characterized in that: The weight ratio of the cellulose ether-modified lithium magnesium silicate to the aliphatic polyisocyanate is 6:

5.

4. The artificial marble according to claim 1, characterized in that: The weight ratio of the cellulose ether modified lithium magnesium silicate to the polyvinyl acetate is 2:

1.

5. The artificial marble according to claim 1, characterized in that: The preparation method of cellulose ether modified lithium magnesium silicate comprises the following steps: taking an appropriate amount of water, first adding cellulose ether to disperse evenly, then adding lithium magnesium silicate to continue to disperse evenly, and then drying to remove water to obtain the cellulose ether modified lithium magnesium silicate.

6. The artificial marble according to claim 5, characterized in that: The weight ratio of the lithium magnesium silicate to the cellulose ether is 1:0.2-0.

5.

7. The artificial marble according to claim 1, characterized in that: The cellulose ether is a mixture of hydroxyethyl cellulose 250HBR and hydroxyethyl cellulose 250HHBR.

8. The artificial marble according to claim 7, characterized in that: The weight ratio of the hydroxyethyl cellulose 250HBR to the hydroxyethyl cellulose 250HHBR is 1:

1.

9. The artificial marble according to claim 1, characterized in that: The flame retardant is a silicon-based flame retardant.

10. The method for preparing the artificial marble according to claims 1 to 9, characterized in that: The following steps are involved: Preliminarily mix a set amount of marble powder, polypropylene glycol, cellulose ether-modified lithium magnesium silicate and polyvinyl acetate to obtain a mixture; Add a set amount of aliphatic polyisocyanate and flame retardant into the mixture and continue to mix well, then add dibutyltin dilaurate and stir well to obtain a pre-cured material; The pre-cured material is put into a mold for compression molding, and then is heat-cured by heat preservation and then cooled and demoulded to obtain the artificial marble.

Citation Information

Patent Citations

  • Flame-retardant and heatproof artificial stone with high hardness and luster

    CN104829169A

  • Waterproof coating, preparation method thereof and waterproof system containing same as well as construction method

    CN108034347A

  • High-performance organic artificial marble and preparation method thereof

    CN115872670A

  • Magnesium lithium silicate modified carboxymethyl cellulose ether and lithium ion battery negative electrode slurry prepared from magnesium lithium silicate modified carboxymethyl cellulose ether

    CN118063861A

  • Organic-inorganic polymers with good mechanical properties - are prepd. by reacting poly:isocyanate with poly:silicic acid component in presence of phosphoric acid ester or ester-salt as reactive diluent

    DE4121153A1